2015
DOI: 10.1177/1933719114557897
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Lower Doses of Mifepristone Combined With Misoprostol for the Termination of Ultra-Early Pregnancy: A Dose-Ranging Randomized Controlled Trial

Abstract: This study aimed to investigate the effectiveness and safety of lower doses of mifepristone combined with misoprostol for the termination of ultra-early pregnancy. A total of 2500 women with ultra-early pregnancy (amenorrhea ≤ 35 days) were randomly divided into 5 groups with gradually decreased dose of oral mifepristone from 150 to 50 mg followed by 200 µg of oral misoprostol 24 hours later. The primary end point was complete abortion without surgical intervention. Secondary end points were vaginal bleeding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 18 publications
3
30
0
1
Order By: Relevance
“…The present results demonstrated that self‐administration of low‐dose misoprostol following mifepristone is as safe and effective as an equivalent dose regimen with hospital‐administered misoprostol, with the H‐Mis and S‐Mis groups in this study experiencing similar success rates and occurrence rates for side effects. These findings extend our earlier findings showing that low‐dose mifepristone combined with misoprostol could is a safe and effective method of very early pregnancy termination (≤35 days of amenorrhoea) or emergency contraception …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The present results demonstrated that self‐administration of low‐dose misoprostol following mifepristone is as safe and effective as an equivalent dose regimen with hospital‐administered misoprostol, with the H‐Mis and S‐Mis groups in this study experiencing similar success rates and occurrence rates for side effects. These findings extend our earlier findings showing that low‐dose mifepristone combined with misoprostol could is a safe and effective method of very early pregnancy termination (≤35 days of amenorrhoea) or emergency contraception …”
Section: Discussionsupporting
confidence: 90%
“…found that reducing the mifepristone dose by two thirds, from 600 to 200 mg, reduced adverse effects without reducing efficacy . Furthermore, in large‐scale studies, our research group has found that efficacy for very early pregnancy termination was maintained with even lower doses of mifepristone (50–150 mg) combined with low‐dose misoprostol (200–400 μg), with similar minor side effects being observed across these dose ranges and with the lower dosages resulting in less irregular uterine bleeding . More recently, in 2015, we found that with very‐low‐dose mifepristone (50 mg) and misoprostol (200 μg) taken at the time of expected menstruation was efficacious and highly acceptable as a routine (or emergency) contraceptive .…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations